Adolescent motherhood in under 100 000 inhabitants communities in the first decades of the millennium - Aremis Villalobos; Celia Hubert; María I Hernández-Serrato; Elvia de la Vara-Salazar; Leticia Suárez-López; Martín Romero-Martínez; Leticia Ávila-Burgos; Tonatiuh Barrientos (Instituto Nacional de Salud Pública, 2019)
Objective. To analyze the adolescent motherhood trend and associated factors in under-100 000-inhabitants communities. Materials and methods. Cross-sectional analysis of 16 686 women in under-100 000-inhabitants communities in Encuesta Nacional de Salud y Nutrición (Ensanut) 2006, 2012 and 100k 2018. We adjusted robust Poisson models with adolescent motherhood as dependent variable for women aged 12-19 and 20-24. Results. Attending school and using modern contraceptives decrease adolescent motherhood prevalence in both age groups. Among adolescent girls, having a health financing scheme, and early sexual debut in the case of adults, is positively associated with adolescent motherhood. Conclusions. It is necessary to strengthen public policies seeking to modify structural factors that provide life choices, and to maintain and strengthen the actions and coverage proposed by Estrategia Nacional para la Prevención del Embarazo en Adolescentes (ENAPEA) targeting this population.